Epidemiology of horse pythiosis in the Pantanal of Mato Grosso: Exploring the host-parasite-vector relationship - dos Santos, Carlos E.P. [UNESP]; Loreto, Erico S.; Zanette, Régis A.; Santurio, Janio M.; Marques, Luis C. [UNESP] (Elsevier, 2024)
Horse pythiosis is considered an endemic disease in the Brazilian Pantanal region, causing devastating health and economic losses. This study aimed to enhance the understanding of pythiosis epidemiology, map the distribution of horse body lesions, and investigate the correlation between these lesions and warm body surface areas, potentially implicating hematophagous vectors in the disease's transmission. A prospective study was conducted on equids in the Pantanal Mato-grossense and adjacent areas from 2012 to 2022, with 112 horses and three mules diagnosed with pythiosis. Clinical and epidemiological data, lesions' photographic records, and healthy equids' thermal imaging were collected. Most pythiosis cases occurred between January and March, correlating with regional flood cycles. Most lesions were found on limbs and the ventral abdomen, with dark-colored horses exhibiting a higher frequency of lesions. Interestingly, the thermal mapping revealed that warm areas on a healthy horse's body overlapped significantly with lesion distribution – blood-sucking insects also prefer these areas. The results suggest that pythiosis lesions in horses correlate with warmer areas of the animal body, reinforcing the hypothesis of vector involvement in disease transmission. This study underscores the need for further observational research to fully understand the complex epidemiological dynamics of pythiosis in horses.
Keywords: Epidemiology; Hematophagous vectors; Horses; Lesion distribution; Pythiosis; Thermography